Penguatan Karakter Islami pada Anak Usia Dini dengan Media Permainan Tradisional yang Disesuaikan dengan Nilai Nilai Islam - Ade Ismail Fahmi; Hasanah; Siti Aliyah; Nur Aini Zaida; Naila Attamimi (CV. Creative Tugu Pena, 2024)
Traditional games are an important part of local culture that can be used as a learning medium to strengthen Islamic character in early childhood. This community service activity aims to integrate Islamic values ​​into traditional games to support character formation in RA Cahaya Iman students. The method used is the Asset-Based Community Development (ABCD) approach, which actively involves the community in planning, implementing and evaluating the program. The subjects of this activity include teachers, parents and students of RA Cahaya Iman, with intensive training and assistance related to traditional Islamic game-based learning media. The results of the activity show that this approach has succeeded in increasing children's understanding of the values ​​of honesty, responsibility and discipline through game media such as